Antimicrobial properties and toxity test of ajwa date [pheonix dactylifera l.] seeds, stingless bee honey [trigona Itama] and their combinations / Nurul Syazwina Roslan - Roslan, Nurul Syazwina (2020)
Skin diseases are one of the major diseases that were recorded to origin from bacteria. Some of these bacteria have mutates into multidrug-resistance bacteria where current treatment or drugs are becoming less effective towards these mutant bacteria. This study focused on identifying the antibacterial properties and the toxicity of stingless bee honey and Ajwa date seeds through disc diffusion assay and brine shrimp lethality assay. The effectiveness of stingless bee honey and Ajwa date seeds alone and followed with their combinations as antibacterial agent against Staphylococcus aureus and Staphylococcus epidermidis were tested through disc diffusion assay. The toxicity of the samples was tested through cytotoxicity test of brine shrimp lethality assay. Based on the result both samples of stingless bee honey and Ajwa date seeds alone exhibit zone of inhibition with diameter of 9.67 mm for Ajwa date seeds alone against Staphylococcus aureus and 10.17 mm for stingless bee honey against Staphylococcus epidermidis at concentration of 100 μg/ml. 1:1 combinations of both samples showed an increment against both bacteria as compared alone with diameter of 13.33 mm respectively for both Staphylococcus aureus and Staphylococcus epidermidis. The composition that contribute to the higher increment of their antibacterial properties are due to the presence of hydrogen peroxide in stingless bee honey and also phenolic content of Ajwa date seeds such as oleic and lauric acid. The toxicity of stingless bee honey and Ajwa date seeds were determined using cytotoxicity test as to determine the toxicity value of both sample that qualify them to have the potency to act as drugs. It is found that both samples of stingless bee honey and Ajwa date seeds are toxic against cancer cell line with LC50 value of 254.474 μg/ml and 391.918 μg/ml. For combination, all ratio exhibited the same percent of mortality with value of 40% respectively. As conclusion, this study proved that stingless bee honey and Ajwa date seeds have the antimicrobial properties that can fight against multidrug resistance bacteria and have a high potential in becoming the new source as for combating skin infections bacteria.